PENERAPAN ALGORITMA K-MEANS CLUSTERING UNTUK PENCATATAN PENCAPAIAN KINERJA KARYAWAN - Imam Utomo; Ilka Zufria; Muhammad Siddik Hasibuan (Smart Education, 2024)
Abstract: This study aims to classify employee performance using the K-Means method. Employee data includes total orders, average order processing time, customer satisfaction, delivery errors, absences, successful projects, and training attended. The clustering process begins with calculating the initial centroid distance and grouping the data based on the nearest distance, repeated until there are no significant changes in the centroid positions. Clustering results are displayed in the